2019
DOI: 10.1029/2019ja026913
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Distribution of Whistler Mode Waves in the Radiation Belts With Large Magnetic Field Amplitudes and Comparison to Large Electric Field Amplitudes

Abstract: We present a statistical analysis with 100% duty cycle and non‐time‐averaged amplitudes of the prevalence and distribution of high‐amplitude >50‐pT whistler mode waves in the outer radiation belt using 5 years of Van Allen Probes data. Whistler mode waves with high magnetic field amplitudes are most common above L=4.5 and between magnetic local time of 0–14 where they are present approximately 1–6% of the time. During high geomagnetic activity, high‐amplitude whistler mode wave occurrence rises above 25% in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…This corresponds to the duskside region, near the inner edge of the outer radiation belt, outside the plasmapause. This region is outside of the peak location of chorus observations, which is on the dawn and dayside, particularly at times of low to moderate geomagnetic activity, but well within the region of observed chorus waves (Li et al, 2016;Tyler et al, 2019aTyler et al, , 2019b. Latitudinally, at 0145 UT, the two satellites are at~12°M LAT (RBSP A) and~21°MLAT (Arase).…”
Section: 1029/2020ja028315mentioning
confidence: 66%
“…This corresponds to the duskside region, near the inner edge of the outer radiation belt, outside the plasmapause. This region is outside of the peak location of chorus observations, which is on the dawn and dayside, particularly at times of low to moderate geomagnetic activity, but well within the region of observed chorus waves (Li et al, 2016;Tyler et al, 2019aTyler et al, , 2019b. Latitudinally, at 0145 UT, the two satellites are at~12°M LAT (RBSP A) and~21°MLAT (Arase).…”
Section: 1029/2020ja028315mentioning
confidence: 66%
“…Landau resonance due to chorus waves may contribute to the enhancement of low pitch angle electrons at energies below several hundred eV especially when the waves are oblique (e.g., Li et al, 2019;Ma et al, 2017). The highly oblique chorus waves or the quasi-electrostatic whistler mode waves (Li et al, 2016;Tyler et al, 2019) are not included in our statistical survey. The large electric field component of the waves compared to the magnetic field component indicates the effects of Landau resonance (e.g., Agapitov et al, 2018), which potentially leads to the energetic 10.1029/2020GL088798 electron flux enhancement (e.g., Artemyev et al, 2016).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Although the universal applicability of quasilinear theory is called into question by the presence of discrete, large‐amplitude chorus (e.g., Cattell et al, 2008; Cully et al, 2008; Kellogg et al, 2011; Tyler et al, 2019; Wilson et al, 2011), test particle simulations have demonstrated its general validity for small amplitude and broadband waves (Tao et al, 2011). Moreover, recent multidimensional diffusion simulations reproduced the main features of observed radiation belt electron dynamics (Albert et al, 2009; Drozdov et al, 2015; Fok et al, 2008; Fok et al, 2014; Glauert et al, 2014; W. Li, Ma, et al, 2016; Ma et al, 2018; Shprits et al, 2009; Thorne et al, 2013a; Tu et al, 2014; Xiao et al, 2014; Zheng et al, 2014).…”
Section: Local Energy and Pitch Angle Scatteringmentioning
confidence: 99%